On Querdenken, Reichsbürger and the Patriotic Union: Exploring the Formation of an Anti-Government Extremist Network in Germany - Heyn, Leoni (Perspectives on terrorism, 2025)
This article examines the digital convergence of distinct extremist milieus involved in the Patriotic Union’s thwarted plot to overthrow the German government in December 2022. By specifically investigating the merging process of involved digital networks of the German Corona-protest and Sovereign Citizens milieu over time, this article analyses the event’s broader implications for the German extremism landscape linked to the transnational evolution of anti-government extremism (AGE). Empirically, this study explores the relationship between issue-driven AGE (Querdenken) and ideologically driven AGE (Reichsbürger) by conducting a longitudinal network analysis of 785,865 Telegram messages from the attempted storming of the Reichstag (August 2020) until the events of December 2022. The analysis reveals a 25.6 percent overlap between Querdenken and Reichsbürger channels, indicating a formation process of a new small, yet notable AGE network. Further, the article finds that the highest spikes of convergence occur in intervals correlating with large-scale offline events, suggesting a feedback loop of offline encounters and online convergence. Thus, this study contributes not only to a dearth of literature on German-centred extremism and transnational debates on their changing nature reflected in the growing body of research on AGE. This study also offers empirical insights into group-level online radicalisation processes.